2021
DOI: 10.1002/adtp.202000274
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembling Nanofibers Inhibit Inflammation in a Murine Model of Crohn's‐Disease‐Like Ileitis

Abstract: Inflammatory bowel diseases are characterized by chronic inflammation, leading to the destruction of gastrointestinal tract tissue. Strategies specifically utilized to manage intestinal inflammation in patients afflicted with Crohn's disease (CD) are met with numerous obstacles. These include treatment‐specific physiological side effects and the development of resistance to biological and pharmacological therapies. As an alternative treatment approach, high aspect ratio supramolecular anti‐inflammatory peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Nanostructured supramolecular polymers (SPs) can be viewed as one-dimensional assemblies with a high degree of internal order. Depending upon their chemical structures and assembly pathways, the resultant SPs can assume various morphologies such as nanofibers, nanoribbons, and nanotubes, among others. The one dimensionality at the supramolecular level is largely rooted in the directional, strong, associative interactions at the molecular level, such as hydrogen bonding and π–π stacking, yet it could also be a result of achieving an optimal interfacial surface area stabilized by a spontaneous curvature that favors a cylindrical packing geometry. , For molecular building units such as peptide amphiphiles that contain a β-sheet-forming peptide motif, the complex interplay of enthalpic interactions stemming from its peptidic traits and those from its amphiphilic features allows for access to a diverse array of SPs of varying sizes and shapes; , however, Y-junctions, or three-way connections that have been theoretically predicted and experimentally observed as a topological defect in cylinder-forming traditional surfactant systems, have not been identified as stable structures in peptide-based supramolecular polymeric systems.…”
mentioning
confidence: 99%
“…Nanostructured supramolecular polymers (SPs) can be viewed as one-dimensional assemblies with a high degree of internal order. Depending upon their chemical structures and assembly pathways, the resultant SPs can assume various morphologies such as nanofibers, nanoribbons, and nanotubes, among others. The one dimensionality at the supramolecular level is largely rooted in the directional, strong, associative interactions at the molecular level, such as hydrogen bonding and π–π stacking, yet it could also be a result of achieving an optimal interfacial surface area stabilized by a spontaneous curvature that favors a cylindrical packing geometry. , For molecular building units such as peptide amphiphiles that contain a β-sheet-forming peptide motif, the complex interplay of enthalpic interactions stemming from its peptidic traits and those from its amphiphilic features allows for access to a diverse array of SPs of varying sizes and shapes; , however, Y-junctions, or three-way connections that have been theoretically predicted and experimentally observed as a topological defect in cylinder-forming traditional surfactant systems, have not been identified as stable structures in peptide-based supramolecular polymeric systems.…”
mentioning
confidence: 99%
“…Other PA morphologies do not (Figure S12). This morphological similarity between PA SBs and dECM, combined with the ability to tailor the biological signals present on PA, , suggests that SBs can serve as morphological mimics of dECM with reduced batch-to-batch variability and greater structural uniformity than naturally derived scaffolds. , …”
Section: Resultsmentioning
confidence: 99%
“…Self-assembling PAs have demonstrated utility in a wide range of settings and applications. [144][145][146][147][148][149][150] PAs are comprised of a hydrophobic alkyl segment attached to a peptide domain that includes a β-sheet forming segment (Figure 4). In aqueous environments, these molecules self-assemble through hydro-phobic collapse of the alkyl domain in combination with hydrogen bonding in the β-sheet domain to produce high aspect-ratio nanofibers.…”
Section: Nanomolecular Treatment Optionsmentioning
confidence: 99%
“…[144,147] Recently, Bury et al have demonstrated the efficacy of PAs that express a potent anti-inflammatory peptide, known as TxPAs, in the established mouse model (SAMP1/YitFc) of CD-like ileitis. [150] As a proof of concept study, inflammatory lesions identified in the ileum of SAMP1/YitFc mice were directly injected with the Tx-PA. Several key inflammatory metrics were positively modulated by Tx-PA treatment. Observed was a statistically significant reduction in mean lesion size of the treatment group (Tx-PA) when comparing treatment PA controls [(un-injected (NO INJ); saline-injected (SAL), and control PA (C-PA) mice)].…”
Section: Nanomolecular Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation